The role of strategic awareness in investment decisions : field research (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to test the effect of strategic awareness (external, internal, current and future) as an independent variable in investment decisions (suitability, acceptance and quality) as a dependent variable on a sample of the Ministry of Planning represented by (62) directors and department heads. It relied on the descriptive analysis method using a questionnaire and using...  Statistical methods: The arithmetic mean, standard deviation, and coefficient of variation, and using the (spssV2020) program. The most prominent results were the presence of a statistically significant effect of the dimensions of strategic awareness on the dimensions of investment decisions.  Important results were reached that showed a strong role for the relationship between the two independent variables and their impact in reducing barriers to achieving strategic goals.